2015
DOI: 10.1186/s12889-015-1436-8
|View full text |Cite
|
Sign up to set email alerts
|

Causes of suicidal behaviors in men who have sex with men in China: a national questionnaire survey

Abstract: BackgroundMen who have sex with men (MSM) have become a high-risk group of HIV infection in China. To date, little is known regarding the psychological characteristics in Chinese MSM, especially the prevalence of suicidal ideation and attempts.MethodsA questionnaire survey was conducted on 2,250 MSM recruited from gay bars in 9 large cities in mainland China. Data on the prevalence of suicidal ideation and attempts as well as the underlying causes in the respondents were analyzed.ResultsA total of 1530 MSM res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…The 12‐month prevalences of suicidal ideation (9.7%), plan (4.0%), and attempt (3.0%) in our cohort of Chinese MSM were similar to the 12‐month rates from a recent survey of young Chinese LGBs in Shanghai (ideation: 9.43%, attempt: 2.53%) (Lian, Zuo, Lou, Gao, & Cheng, ), the 6‐month rates of Chinese MSM in Mianyang City (ideation: 9.0%, plan: 4.5%, attempt: 3.5%) (Wang et al, ), and Hefei City (ideation: 10.5%, attempt: 3.9%) (Zhang et al, ), but lower than the lifetime prevalences of MSM in 9 large cities in China (ideation: 26.0%, attempt: 12.6%) (Chen, Li, Wang, & Zhang, ), and the 6‐month prevalence in Wuhan City (ideation: 18.6%, attempt: 10.7%) (Zheng et al, ). However, it is difficult to compare these previous results with our results because the study populations had major differences in age structure and used different definitions of suicidal behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…The 12‐month prevalences of suicidal ideation (9.7%), plan (4.0%), and attempt (3.0%) in our cohort of Chinese MSM were similar to the 12‐month rates from a recent survey of young Chinese LGBs in Shanghai (ideation: 9.43%, attempt: 2.53%) (Lian, Zuo, Lou, Gao, & Cheng, ), the 6‐month rates of Chinese MSM in Mianyang City (ideation: 9.0%, plan: 4.5%, attempt: 3.5%) (Wang et al, ), and Hefei City (ideation: 10.5%, attempt: 3.9%) (Zhang et al, ), but lower than the lifetime prevalences of MSM in 9 large cities in China (ideation: 26.0%, attempt: 12.6%) (Chen, Li, Wang, & Zhang, ), and the 6‐month prevalence in Wuhan City (ideation: 18.6%, attempt: 10.7%) (Zheng et al, ). However, it is difficult to compare these previous results with our results because the study populations had major differences in age structure and used different definitions of suicidal behaviors.…”
Section: Discussionsupporting
confidence: 84%
“…Psychological processes resulting from sexual stigma may maintain or exacerbate poor mental health, ultimately influencing behaviors that put MSM at risk of new infections. [57] Understanding the mental health processes in these pathways may allow an intervention point to prevent further transmission.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have shown a direct relationship between sexual stigma and suicidal ideation[47] and there is growing evidence that suicidal ideation is a significant problem for MSM across sub-Saharan Africa (SSA). [810] Suicidal ideation is often associated with cognitive processes including hopelessness, pessimism, negative self-perceptions, and poor problem-solving skills that may hinder protective health behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Most research on MSM in China has focused on demographic characteristics, sexual behaviors, and HIV infection [34, 35]; only a small number of studies have explored the psychosocial context [36, 37], and even fewer have considered the interacting and overlapping effects of psychosocial factors [11, 12]. In the present study, we investigated the prevalence of psychosocial problems in MSM in Shanghai, to determine if a syndemic of psychosocial problems could increase high-risk sexual behaviors and HIV infection in this population.…”
Section: Introductionmentioning
confidence: 99%